Estudo exploratório de neurocisticercose em achados tomográficos registrados em hospital de Alfenas- MG - Pimentel, Brenda Alves (2019)
Neurocysticercosis (NCC) is a worldwide public health problem, and it is the most common parasitosis that affects the Central Nervous System affecting millions of people all around the world. However, its actual epidemiological situation is still unknown due to the lack of accurate prevalence information about this disease. This survey aimed to know and study the epidemiological profile of the southern region in the state of Minas Gerais, focusing in the city of Alfenas and region. The study began with the process of sampling and analysis of craniofacial computed tomography of a hospital, in Alfenas - MG, corresponding to the year of 2018, in search of tomographic findings compatible with neurocysticercosis; followed by the verification of magnetic resonance imaging of patients with previously identified findings, and the search for possible viable cysticerci, the active form of the disease; After that, data of the patients with findings compatible with NCC were collected, and later organized, classified and discussed. We obtained, then, an overview of the neurocysticercosis’s situation in the region, showing a 10.35% prevalence of NCC’s disease in patients who underwent the neurology service, the predominance of women with 50.63%, majority of the age group from 71 to 80 years, representing 24.69% of the cases, and the cities Alfenas and Campos Gerais with the largest number of identified cases.